The teaching of urban and neighborhood history. The case of San José district of Bogotá - Gilberto Enrique Parada García (Civilizar, 2014)
This article highlights the importance for the development of current historiography, teaching and research in neighborhood history. The article emphasizes the individual’s relationship with his space environment, from the point of view of urban history in Barrio San Jose, south of Bogotá. The methodology is supported by evidence of oral history and research of neighborhood files; from there, this text intends to open a reflection that moves from the micro-social text to the larger historical context of the city and the country. Thus the article examines, first, some important elements of the teaching of urban and neighborhood history and historiography; then, it explains the different social dynamics that intersect in the limited space of a neighborhood; finally, it raises questions about individual and collective historical experiences of the local people.